OPTIMASI ZAT WARNA BUNGA TELANG (Clitoria ternatea) SEBAGAI PEWARNA ALAMI PADA SIRUP PARASETAMOL - Diah Pratimasari; Novena Yety Lindawati (Jurnal Ilmiah Manuntung, 2018)
One of the most developed pharmaceutical preparations for paracetamol is a syrup. An important additional substance required in the formulation of the syrup is a coloring agent. Telang flower (Clitoria ternatea) is one of the plants that has been proved to contain anthocyanins. Anthocyanin is a compound which can be used as a coloring agent. Thus, it is important to further explore telang flower’s potential as a natural coloring agent in paracetamol syrup preparation. This research was started with the extraction of the dye or anthocyanin content in the telang flower. The extraction was performed by ethanol with maceration method. Paracetamol syrups were prepared in four different formulations (F1, F2, F3, and F4). F1, F2, and F3 contained three increased concentrations of telang extract of 0.25%, 0.5% and 1.0%, respectively, while F4 was added with the synthetic food coloring agent, as a control. Each formula was evaluated based on its physical properties parameters including organoleptic observation, pH, density viscosity, and color stability test using spectrophotometry. The results of organoleptic, pH, density viscosity, and color stability parameters showed that telang extract with the concentration of 0.25% and 1% possessed more stable result than 0,5% concentration in the paracetamol syrup preparations.